EMERALD LITERATI AWARD 2016 AWARDED TO 6 USM AUTHORS - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 12 April 2017 - Six authors from Universiti Sains Malaysia (USM) have been awarded the Emerald Literati Award 2016 by Emerald Publishing. The USM Vice-Chancellor, Professor Datuk Dr. Asma Ismail said that the Key Performance Indicator (KPI) for a university is the output of the research in the form of journal publications. "In 2016, USM has published 2326 articles in various journals and USM is always pushing for more articles to be published as it is one of the country’s Research Universities," said Asma.